Nutrient Content of Poultry Feed Used in Different Poultry Farms of Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2008)
As quality of feed is the main determinant factor in successful poultry farming attempts were made to evaluate the quality of feeds used in the farms of Bangladesh. Feed samples were collected from two layer farm, four big hatcheries and six broiler farms located in different areas of Bangladesh and the collection was continued for twelve months. For monitoring the quality, dry matter, crude protein, ether extract, ash and calcium content in the feed were determined. The information regarding the source and ingredients of the feed as well as the feeding practices followed by the farms was also recorded. Based on age, purpose and stage of production, different feeding systems were practiced by the farms. In the present investigation, breeder farms were found to own feed-mill where they produced their feed and the quality of the feed appeared better compared to those used in broiler or layer farms. The nutrient contents in breeder ration were as per recommendation of the strain producing company. A wide variation of nutrient contents was observed in the feed fed to broilers in different farms. When the broiler feed was produced in the own feed-mill of the farm or supplied from a renowned feed- mill, the quality appeared to be quite acceptable with some deviation. Some self-prepared broiler feeds contained higher amount of ash and calcium. The broiler feed from retailer shop was found to be least acceptable. Remarkable fluctuation was noticed in metabolizable energy( ME) and ash content of layer layer feed procured from the retailer shop. Key words: Poultry feed, Nutrient content, Breeder feed, Broiler feed, Layer feed DOI: 10.3329.bjsir.v43i1.852Bangladesh J. Sci. Ind. Res. 43(1), 1-12, 2008